Recognizing Incidences of Unprovoked Attacks Against Police Officers in Nigeria Between 2017-2020: Charting New Pathways of Human Rights Intervention on Right to Life - Nwaechefu, Hilary; Nnawulezi, Uche (Universitas Negeri Semarang (UNNES), 2022)
The unprovoked attacks on Police Officers in Nigeria between 2017-2020 that resulted to several deaths of the Police Officers have put a question mark on the constitutional provisions guaranteeing the rights of all citizen's lives and that of the Police Officers. This paper seeks to identify why the unlawful killings of Police Officers had persisted notwithstanding constitutional provisions. lnterestingly, despite these developments, the position of international human rights law(IHRL) and Section 33 Chapter IV of the Constitution of the Federal Republic of Nigeria, 1999(as amended) has raised two key questions, first, the standards of protection by government. Second, the permissible circumstances in which persons deserves protection. This paper revealed that inadequate equipment, training and rascal attitudes of police officers towards crime prevention led to unlawful attacks on them which resulted to their deaths during the period under review. Recommendations are made towards stemming the tide. The paper adopted a doctrinal approach that focused principally on current legislations and policies on human rights protection, and concluded with the view that the national and international policy makers have a moral, ethical and legal obligations to protect the lives of police officers as they are entitled to such protection based on their human rights and by so doing it will help to compliment the provisions of the Universal Declaration of Human Rights, 1948 as well as Section 33 Chapter IV of the Constitution of the Federal Republic of Nigeria, 1999